Gas sensor based on nanofiber aerogel, preparation method and application thereof
Patent Information
- Application Number
- CN202311200311.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-09-18
- Publication Date
- 2026-10-27
- Estimated Expiration
- 2043-09-18
AI Technical Summary
[0005]本发明的目的是提供一种基于纳米纤维气凝胶的气敏传感器、其制备方法及应用,以解决现有气敏传感固相载体孔隙率低、内部连通差,致使挥发性盐基氮气体分子传质扩散慢的问题
[0025]本发明通过研制凹凸棒石/聚酰亚胺复合纳米纤维气凝胶作为气敏传感固相载体,利用其高孔隙率和3D多级孔道结构使得目标物气体分子在其中传质扩散更容易,由此可与探针分子更快速、充分地接触并发生相互作用,进而提高气敏传感检测的速度和灵敏度,解决了现有气敏传感固相载体孔隙率低、内部连通差的缺陷,应用前景广泛。
Smart Images

Figure CN117647627B_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of sensor technology, specifically to a gas sensor based on nanofiber aerogel, its preparation method, and its application. Background Technology
[0002] Aquatic products are highly susceptible to spoilage during processing, storage, transportation, and sales. Fermentation by bacteria and enzymes produces a putrid odor, primarily composed of volatile basic nitrogen. Therefore, volatile basic nitrogen serves as a crucial indicator for assessing the degree of spoilage in aquatic products. Consuming spoiled aquatic products can cause a range of adverse reactions, and in severe cases, can be life-threatening. Therefore, establishing a rapid and sensitive method for monitoring volatile basic nitrogen to detect early spoilage in aquatic products is of significant practical importance for ensuring the safety of aquatic product consumption.
[0003] Currently, widely used methods for analyzing volatile basic nitrogen include spectrophotometry, headspace gas chromatography, headspace gas chromatography-mass spectrometry, high-performance liquid chromatography-mass spectrometry, ion mobility spectrometry, and capillary electrophoresis. These traditional analytical methods rely on specialized operators, are expensive, time-consuming, labor-intensive, and can cause irreversible damage to aquatic products. Therefore, "olfactory visualization" technologies such as electronic noses have become a research hotspot in the field of volatile basic nitrogen detection. However, the core component of electronic noses is a metal oxide semiconductor gas-sensitive material, which is susceptible to the influence of water vapor in the environment, resulting in moisture aging and inaccurate detection results. Compared to electronic noses and other electronic components, gas sensors offer superior performance in the practical application of volatile basic nitrogen visualization detection: they are simple to operate, provide intuitive results, and require no sample pretreatment, thus enabling rapid and non-destructive detection.
[0004] Current solid-phase supports for the detection of volatile basic nitrogen gases are mainly thin films and filter paper, which require response times of several minutes or even longer, and their sensitivity is not ideal. This is because the solid-phase supports used have low porosity and poor internal connectivity, resulting in slow mass transfer and diffusion of volatile basic nitrogen gas molecules, further affecting the interaction between volatile basic nitrogen gas molecules and probe molecules. Since the spoilage process of aquatic products accelerates and intensifies once spoilage occurs, the performance indicators of existing methods, such as response time and sensitivity, urgently need further improvement to meet the practical needs of detecting early spoilage of aquatic products and ensuring food safety. Therefore, developing solid-phase supports that facilitate gas molecule mass transfer and diffusion is an urgent research topic in the field of rapid and visualized detection of volatile basic nitrogen based on gas-sensitive sensing technology. Summary of the Invention
[0005] The purpose of this invention is to provide a gas sensor based on nanofiber aerogel, its preparation method and application, in order to solve the problem that the existing gas-sensitive solid carrier has low porosity and poor internal connectivity, resulting in slow mass transfer and diffusion of volatile basic nitrogen gas molecules.
[0006] This invention is implemented as follows:
[0007] The gas sensor based on nanofiber aerogel provided by this invention is prepared by freeze-drying a polyimide nanofiber membrane. This process allows water in a frozen nanofiber dispersion containing attapulgite and probe molecules to sublimate directly from the frozen ice solid into vapor without melting the ice, while the nanofibers themselves remain in the ice frame during freezing. The resulting gas sensor, leveraging the high porosity and unique 3D hierarchical pore structure of the nanofiber aerogel, provides a stable and rapid transport channel for the diffusion of volatile basic nitrogen gas molecules. This allows for more thorough contact and interaction between the volatile basic nitrogen and the probe molecules, thereby improving the detection efficiency of the gas sensor.
[0008] The above-mentioned method for preparing the gas sensor based on nanofiber aerogel specifically includes the following steps:
[0009] S1. Prepare a polyimide spinning solution and obtain a polyimide nanofiber membrane by electrospinning.
[0010] S2. The polyimide nanofiber membrane obtained in step S1 is homogenized together with attapulgite and probe molecules to obtain a polyimide short fiber dispersion containing attapulgite and probe molecules.
[0011] S3. The polyimide short fiber dispersion containing attapulgite and probe molecules obtained in step S2 is freeze-dried to obtain an attapulgite / polyimide composite nanofiber aerogel gas sensor.
[0012] Preferably, step S1 is as follows:
[0013] S1-1. Using N,N-dimethylacetamide as a solvent, prepare a polyimide spinning solution with a mass fraction of 25% to 30%, and place it in a syringe. Set the liquid supply rate to 0.5 to 1.0 mL / h, and the nozzle diameter of the syringe to 0.4 to 0.86 mm.
[0014] S1-2. Set the voltage of the high-voltage power supply that provides the high-voltage electrostatic field to 15-20kV, and adjust the distance between the syringe nozzle and the aluminum foil collecting screen to 10-15cm; connect the syringe nozzle to the positive terminal of the high-voltage power supply, and connect the aluminum foil collecting screen to the negative terminal of the high-voltage power supply.
[0015] S1-3. After collecting for 10-12 hours, polyimide nanofiber membranes are obtained.
[0016] Preferably, step S2 is as follows:
[0017] S2-1. Cut the polyimide nanofiber membrane into 1.0cm×1.0cm fragments and then immerse them in a solvent; the solvent is tert-butanol or a mixture of tert-butanol and water; the mass fraction of the polyimide nanofiber membrane is 0.5-1.0wt%.
[0018] S2-2, Add attapulgite to the solvent described in step S2-1; the mass fraction of attapulgite is 1.0 to 3.0 wt%.
[0019] S2-3. Add a pH-responsive probe molecule to the solvent described in step S2-1; the pH-responsive probe molecule is any one of thymol blue, neutral red, m-cresol purple, phenol red, cresol red, anthocyanin, alizarin, and curcumin; the mass fraction of the pH-responsive probe molecule is 0.01 to 0.05 wt%.
[0020] S2-4. The polyimide nanofiber membrane, attapulgite, and probe molecules were homogenized together at a homogenization speed of 10,000 rpm for 10 min to obtain a polyimide short fiber dispersion containing attapulgite and probe molecules.
[0021] Preferably, step S3 is as follows:
[0022] S3-1. Place the polyimide short fiber dispersion containing attapulgite and probe molecules in a refrigerator for freezing; the freezing temperature is -80 to -20℃; the freezing time is 5 to 10 hours.
[0023] S3-2. The frozen polyimide short fiber dispersion containing attapulgite and probe molecules was placed in a freeze dryer and dried under a vacuum of 5 Pa for 24 h to obtain an attapulgite / polyimide composite nanofiber aerogel gas sensor.
[0024] The gas sensor prepared by the above method can be used to detect volatile basic nitrogen gas molecules. Compared with existing gas sensors, when using the present invention to detect volatile basic nitrogen gas molecules, it can not only effectively shorten the response time, but also significantly improve the sensing sensitivity, thereby comprehensively improving the sensing performance.
[0025] This invention develops attapulgite / polyimide composite nanofiber aerogel as a solid-phase carrier for gas sensing. Its high porosity and 3D hierarchical pore structure facilitate mass transfer and diffusion of target gas molecules, allowing for faster and more complete contact and interaction with probe molecules. This improves the speed and sensitivity of gas sensing detection, overcoming the shortcomings of low porosity and poor internal connectivity in existing gas-sensing solid-phase carriers, and has broad application prospects. Attached Figure Description
[0026] Figure 1 This is a schematic diagram of the preparation method of the gas sensor based on nanofiber aerogel in this invention.
[0027] Figure 2 This is a scanning electron microscope image of the attapulgite / polyimide composite nanofiber aerogel gas sensor prepared in Example 1 of this invention.
[0028] Figure 3 This is a comparison chart of the detection results of volatile basic nitrogen in whiteleg shrimp stored at 4°C using the gas sensor in Example 1 of this invention and the TVB-N content calculated by the automatic Kjeldahl nitrogen determination method (GB 2733-2015).
[0029] Figure 4 This is a comparison chart of the detection results of volatile basic nitrogen in basa fish stored at 4°C using the gas sensor in Example 1 of this invention and the TVB-N content calculated by the automatic Kjeldahl nitrogen determination method (GB 2733-2015). Detailed Implementation
[0030] The gas sensor based on nanofiber aerogel provided by this invention refers to a gas sensor made based on nanofiber aerogel. Specifically, the nanofiber aerogel is an attapulgite / polyimide composite nanofiber aerogel. The nanofiber aerogel is made by freeze-drying a nanofiber dispersion containing attapulgite and probe molecules, which allows the water in the frozen nanofiber dispersion to sublimate directly from the ice solid to vapor without melting the ice. The nanofibers themselves remain in the ice frame during freezing. When using the gas sensor based on nanofiber aerogel of this invention to detect volatile basic nitrogen gas molecules, the nanofiber aerogel can exert its unique advantages: the nanofiber aerogel not only has primary pores caused by the presence of gaps between fibers, but also honeycomb-like secondary pores caused by the removal of solvent crystals, giving it high porosity and a unique 3D multi-level channel structure. This special morphological feature can provide a stable and rapid transport channel for the diffusion of gas molecules, allowing volatile basic nitrogen molecules to come into more full contact with and interact with probe molecules. This can not only effectively shorten the response time, but also greatly improve the sensing sensitivity, thereby comprehensively improving the sensing performance.
[0031] Combination Figure 1 The method for preparing a gas sensor based on nanofiber aerogel according to the present invention includes the following steps:
[0032] Step 1: Prepare a polyimide spinning solution and obtain a polyimide nanofiber membrane by electrospinning;
[0033] Step 2: Homogenize the polyimide nanofiber membrane obtained in Step 1 with attapulgite and probe molecules to obtain a polyimide short fiber dispersion containing attapulgite and probe molecules.
[0034] Step 3: Freeze-dry the polyimide short fiber dispersion containing attapulgite and probe molecules obtained in Step 2 to obtain an attapulgite / polyimide composite nanofiber aerogel gas sensor.
[0035] in,
[0036] In step 1, the polyimide nanofiber membrane is prepared according to the following steps:
[0037] Step 1-1: Prepare a polyimide spinning solution with a mass fraction of 25% to 30% using N,N-dimethylacetamide as a solvent, and place it in a microsyringe. Set the liquid supply rate to 0.5 to 1.0 mL / h and the nozzle orifice diameter to 0.4 to 0.86 mm.
[0038] Steps 1-2: Set the voltage of the high-voltage power supply providing the high-voltage electrostatic field to 15-20kV, and adjust the distance from the syringe nozzle to the aluminum foil collection screen to 10-15cm.
[0039] Steps 1-3: After collecting for 10-12 hours, polyimide nanofiber membranes are obtained.
[0040] In step 2, the polyimide short fiber dispersion containing attapulgite and probe molecules is prepared according to the following steps:
[0041] Step 2-1: Cut the polyimide nanofiber membrane into pieces of approximately 1.0cm × 1.0cm, and then immerse them in a solvent;
[0042] Step 2-2: Add attapulgite to the solvent mentioned above;
[0043] Steps 2-3: Add pH-responsive probe molecules to the above solvent;
[0044] Steps 2-4: Homogenize the polyimide nanofiber membrane with attapulgite and probe molecules at a homogenization speed of 10,000 rpm for 10 min to obtain a polyimide short fiber dispersion containing attapulgite and probe molecules.
[0045] In step 3, the attapulgite / polyimide composite nanofiber aerogel gas sensor is prepared according to the following steps:
[0046] Step 3-1: Place the polyimide short fiber dispersion containing attapulgite and probe molecules in a refrigerator for freezing;
[0047] Step 3-2: Place the frozen polyimide short fiber dispersion containing attapulgite and probe molecules in a freeze dryer and dry it under a vacuum of 5 Pa for 24 h to obtain an attapulgite / polyimide composite nanofiber aerogel gas sensor.
[0048] In step 2-1, the solvent is any one of tert-butanol, tert-butanol / water (9:1, v / v), tert-butanol / water (8:2, v / v), tert-butanol / water (7:3, v / v), or tert-butanol / water (5:5, v / v).
[0049] In step 2-1, the mass fraction of the polyimide nanofiber membrane is 0.5–1.0 wt%.
[0050] In step 2-2, the mass fraction of the attapulgite is 1.0 to 3.0 wt%.
[0051] In steps 2-3, the pH-responsive probe molecule is any one of thymol blue, neutral red, m-cresol purple, phenol red, cresol red, anthocyanin, alizarin, and curcumin.
[0052] In steps 2-3, the mass fraction of the pH-responsive probe molecule is 0.01–0.05 wt%.
[0053] In step 3-1, the freezing temperature is -80 to -20°C; the freezing time is 5 to 10 hours.
[0054] The present invention will now be described in detail with reference to specific embodiments. In the following embodiments, processes and methods not described in detail are all conventional methods known in the art, and the reagents used are all commercially available analytical grade or chemically pure. The following embodiments all achieve the inventive objectives of the present invention.
[0055] Example 1
[0056] (1) Preparation of polyimide nanofiber membrane
[0057] A 25% (w / w) polyimide spinning solution was prepared using N,N-dimethylacetamide as a solvent and placed in a microsyringe. The injection rate was set to 1.0 mL / h, and the nozzle orifice diameter was 0.86 mm. The nozzle was connected to the positive terminal of a high-voltage power supply, and the aluminum foil collection screen was connected to the negative terminal. The injection voltage was set to 15 kV, and the distance between the stainless steel needle and the aluminum foil collection screen was adjusted to 15 cm. After collecting for 12 hours, a polyimide nanofiber membrane was obtained.
[0058] (2) Preparation of polyimide short fiber dispersion containing attapulgite and probe molecules
[0059] The polyimide nanofiber membrane obtained in step (1) was cut into fragments of about 1.0cm × 1.0cm. 100mg of the polyimide nanofiber membrane fragments were weighed and immersed in 20g of tert-butanol / water (5:5, v / v). Then, 100mg of attapulgite and 10mg of anthocyanin were added. The polyimide nanofiber membrane, attapulgite and anthocyanin were homogenized together at a homogenization speed of 10000rpm for 30min to obtain a polyimide short fiber dispersion containing attapulgite and anthocyanin.
[0060] (3) Preparation of attapulgite / polyimide composite nanofiber aerogel gas sensor
[0061] The polyimide short fiber dispersion containing attapulgite and anthocyanin obtained in step (2) was placed in a -20°C freezer for 10 hours. Then, the frozen polyimide short fiber dispersion containing attapulgite and anthocyanin was placed in a freeze dryer and dried under a vacuum of 5 Pa for 24 hours to obtain an attapulgite / polyimide composite nanofiber aerogel gas sensor.
[0062] Example 2
[0063] (1) Preparation of polyimide nanofiber membrane
[0064] A 28% (w / w) polyimide spinning solution was prepared using N,N-dimethylacetamide as a solvent and placed in a microsyringe. The injection rate was set to 0.5 mL / h, and the nozzle orifice diameter was 0.6 mm. The nozzle was connected to the positive terminal of a high-voltage power supply, and the aluminum foil collection screen was connected to the negative terminal. The injection voltage was set to 15 kV, and the distance between the stainless steel needle and the aluminum foil collection screen was adjusted to 15 cm. After collecting for 12 hours, a polyimide nanofiber membrane was obtained.
[0065] (2) Preparation of polyimide short fiber dispersion containing attapulgite and probe molecules
[0066] The polyimide nanofiber membrane obtained in step (1) was cut into fragments of about 1.0cm × 1.0cm. 100mg of the polyimide nanofiber membrane fragments were weighed and immersed in 20g of tert-butanol / water (8:2, v / v). Then, 150mg of attapulgite and 5mg of neutral red were added. The polyimide nanofiber membrane, attapulgite and neutral red were homogenized together at a homogenization speed of 10000rpm for 30min to obtain a polyimide short fiber dispersion containing attapulgite and neutral red.
[0067] (3) Preparation of attapulgite / polyimide composite nanofiber aerogel gas sensor
[0068] The polyimide short fiber dispersion containing attapulgite and neutral red obtained in step (2) was placed in a -40°C freezer for 8 hours. Then, the frozen polyimide short fiber dispersion containing attapulgite and neutral red was placed in a freeze dryer and dried under a vacuum of 5 Pa for 24 hours to obtain an attapulgite / polyimide composite nanofiber aerogel gas sensor.
[0069] Example 3
[0070] (1) Preparation of polyimide nanofiber membrane
[0071] A 28% (w / w) polyimide spinning solution was prepared using N,N-dimethylacetamide as a solvent and placed in a microsyringe. The injection rate was set to 1.0 mL / h, and the nozzle orifice diameter was 0.86 mm. The nozzle was connected to the positive terminal of a high-voltage power supply, and the aluminum foil collection screen was connected to the negative terminal. The injection voltage was set to 18 kV, and the distance between the stainless steel needle and the aluminum foil collection screen was adjusted to 15 cm. After collecting for 10 hours, a polyimide nanofiber membrane was obtained.
[0072] (2) Preparation of polyimide short fiber dispersion containing attapulgite and probe molecules
[0073] The polyimide nanofiber membrane obtained in step (1) was cut into fragments of about 1.0cm × 1.0cm. 150mg of the polyimide nanofiber membrane fragments were weighed and immersed in 20g of tert-butanol. Then, 200mg of attapulgite and 3mg of thymol blue were added. The polyimide nanofiber membrane, attapulgite and thymol blue were homogenized together at a homogenization speed of 10000rpm for 30min to obtain a polyimide short fiber dispersion containing attapulgite and thymol blue.
[0074] (3) Preparation of attapulgite / polyimide composite nanofiber aerogel gas sensor
[0075] The polyimide short fiber dispersion containing attapulgite and thymol blue obtained in step (2) was placed in a -60℃ freezer for 8 hours. Then, the frozen polyimide short fiber dispersion containing attapulgite and thymol blue was placed in a freeze dryer and dried under a vacuum of 5 Pa for 24 hours to obtain an attapulgite / polyimide composite nanofiber aerogel gas sensor.
[0076] Example 4
[0077] (1) Preparation of polyimide nanofiber membrane
[0078] A 30% (w / w) polyimide spinning solution was prepared using N,N-dimethylacetamide as a solvent and placed in a microsyringe. The injection rate was set to 0.5 mL / h, and the nozzle orifice diameter was 0.86 mm. The nozzle was connected to the positive terminal of a high-voltage power supply, and the aluminum foil collection screen was connected to the negative terminal. The injection voltage was set to 20 kV, and the distance between the stainless steel needle and the aluminum foil collection screen was adjusted to 15 cm. After collecting for 10 hours, a polyimide nanofiber membrane was obtained.
[0079] (2) Preparation of polyimide short fiber dispersion containing attapulgite and probe molecules
[0080] The polyimide nanofiber membrane obtained in step (1) was cut into fragments of about 1.0cm × 1.0cm. 200mg of the polyimide nanofiber membrane fragments were weighed and immersed in 20g of tert-butanol / water (9:1, v / v). Then, 300mg of attapulgite and 5mg of m-cresol purple were added. The polyimide nanofiber membrane, attapulgite and m-cresol purple were homogenized together at a homogenization speed of 10000rpm for 30min to obtain a polyimide short fiber dispersion containing attapulgite and m-cresol purple.
[0081] (3) Preparation of attapulgite / polyimide composite nanofiber aerogel gas sensor
[0082] The polyimide short fiber dispersion containing attapulgite and m-cresol purple obtained in step (2) was placed in a -80℃ freezer for 5 hours. Then, the frozen polyimide short fiber dispersion containing attapulgite and m-cresol purple was placed in a freeze dryer and dried under a vacuum of 5 Pa for 24 hours to obtain an attapulgite / polyimide composite nanofiber aerogel gas sensor.
[0083] Example 5: Application of the present invention to the detection of volatile basic nitrogen in aquatic products
[0084] The scanning electron microscope image of the attapulgite / polyimide composite nanofiber aerogel gas sensor prepared in Example 1 of this invention is shown below. Figure 2 As shown, the nanofiber aerogel gas sensor not only has primary pores due to the gaps between fibers, but also honeycomb-like secondary pores due to solvent crystal removal. This 3D hierarchical pore structure facilitates faster and more complete contact and interaction between the target gas and probe molecules, thereby effectively improving sensitivity and shortening response time. The attapulgite / polyimide composite nanofiber aerogel gas sensor prepared in Example 1 of this invention was applied to the detection of volatile basic nitrogen in whiteleg shrimp and basa fish stored at 4℃. The detection results are shown below. Figure 3 and Figure 4As shown, the TVB-N content was compared with that calculated using the national standard method—automatic Kjeldahl nitrogen determination (GB 2733-2015). According to GB 2733-2015, the upper limit of TVB-N content in aquatic products is 20 mg / 100g; exceeding this value indicates the beginning of spoilage. Figure 3 As shown, around the fifth day, the TVB-N value of the whiteleg shrimp increased to 20 mg / 100g. At this point, the color difference of the attapulgite / polyimide composite nanofiber aerogel gas sensor was approximately 13.2, indicating that if the color difference value of the whiteleg shrimp is greater than 13.2, then the whiteleg shrimp is not edible. Figure 4 As shown, around the sixth day, the TVB-N value of the basa fish increased to 20 mg / 100g. At this point, the color difference of the attapulgite / polyimide composite nanofiber aerogel gas sensor was 13.1, indicating that if the color difference value of the fish sample is greater than 13.1, the basa fish is inedible. Testing on actual aquatic products demonstrates that the attapulgite / polyimide composite nanofiber aerogel gas sensor is feasible for detecting the degree of spoilage in aquatic products. Compared to the automated Kjeldahl nitrogen determination method, this method has advantages such as being non-destructive and simple to operate when detecting volatile basic nitrogen, and has broad application prospects.
Claims
1. An application of a gas sensor based on nanofiber aerogel, characterized in that, The gas sensor is used to detect volatile basic nitrogen gas molecules. The gas sensor is made by freeze-drying a polyimide nanofiber membrane, in which the water in the frozen nanofiber dispersion containing attapulgite and probe molecules is sublimated directly from the ice solid to vapor without the ice melting, while the nanofiber itself remains in the ice shelf during freezing. The method for preparing the gas sensor based on nanofiber aerogel includes the following steps: S1. Prepare a polyimide spinning solution and obtain a polyimide nanofiber membrane by electrospinning. S2. The polyimide nanofiber membrane obtained in step S1 is homogenized together with attapulgite and probe molecules to obtain a polyimide short fiber dispersion containing attapulgite and probe molecules. S3. The polyimide short fiber dispersion containing attapulgite and probe molecules obtained in step S2 is freeze-dried to obtain an attapulgite / polyimide composite nanofiber aerogel gas sensor. Step S2 is as follows: S2-1. Cut the polyimide nanofiber membrane into 1.0 cm × 1.0 cm fragments and then immerse them in a solvent; the solvent is tert-butanol or a mixture of tert-butanol and water. S2-2, Add attapulgite to the solvent described in step S2-1; S2-3. Add a pH-responsive probe molecule to the solvent described in step S2-1; the pH-responsive probe molecule is any one of thymol blue, neutral red, m-cresol purple, phenol red, cresol red, anthocyanin, alizarin, and curcumin; S2-4. The polyimide nanofiber membrane, attapulgite and probe molecules were homogenized together at a homogenization speed of 10000 rpm for 30 min to obtain a polyimide short fiber dispersion containing attapulgite and probe molecules. In step S2-1, the mass fraction of the polyimide nanofiber membrane is 0.5~1.0 wt%; in step S2-2, the mass fraction of the attapulgite is 1.0~3.0 wt%; and in step S2-3, the mass fraction of the pH-responsive probe molecule is 0.01~0.05 wt%.
2. The application according to claim 1, characterized in that, Step S1 is as follows: S1-1. Using N,N-dimethylacetamide as a solvent, prepare a polyimide spinning solution with a mass fraction of 25%~30%, place it in a syringe, set the liquid supply rate to 0.5~1.0 mL / h, and set the nozzle diameter of the syringe to 0.4~0.86 mm. S1-2. Set the voltage of the high-voltage power supply that provides the high-voltage electrostatic field to 15~20 kV, and adjust the distance between the syringe nozzle and the aluminum foil collecting screen to 10~15 cm; connect the syringe nozzle to the positive terminal of the high-voltage power supply, and connect the aluminum foil collecting screen to the negative terminal of the high-voltage power supply. S1-3. After collecting for 10-12 h, polyimide nanofiber membranes are obtained.
3. The application according to claim 1, characterized in that, Step S3 is as follows: S3-1. Place the polyimide short fiber dispersion containing attapulgite and probe molecules in a refrigerator for freezing; S3-2. The frozen polyimide short fiber dispersion containing attapulgite and probe molecules was placed in a freeze dryer and dried under a vacuum of 5 Pa for 24 h to obtain an attapulgite / polyimide composite nanofiber aerogel gas sensor.
4. The application according to claim 3, characterized in that, In step S3-1, the freezing temperature is -80~-20 ℃; the freezing time is 5~10 h.
Citation Information
Patent Citations
Nano fiber for continuously releasing fragrance and preparation method and application of nano fiber
CN111501128A
Polyimide nanofiber aerogel and preparation method thereof
CN113817216A
Preparation method of asymmetric wettability polyimide fiber-based photo-thermal aerogel
CN115651265A